The Significance Of Chronological Order Of Surahs On Antioxidants In Madaniyyah Context - Nurul Mukminah Zainan Nazri; Wan Nasyrudin Wan Abdullah; Latifah Abdul Majid; Fadlan Mohd Othman (Centre of Islamic Heritage Sustainability, UKM, 2024)
Volume: 6 No: 1 (pages: 69-79)